Complete bladder duplication by a transversal septum with pelvic ectopic kidney - HOUNNASSO, PRINCE PASCAL; AVAKOUDJO, JOSUÉ DEJINNIN GEORGES; DJIALIRI, Malick; SOUMANOU, Fouad Kolawale Yde (My University, 2016)
Bladder duplication is an unusual and congenital abnormality that is usually associated with other abnormalities. We reported the first case in a 16-year-old child who has complete bladder duplication by a tranversal septum. No duplication of the urethra was noted. The pelvic ectopic right kidney was associated with this duplication. The treatment was a right nephroureterectomy with upper bladder bag resection.
Keywords: bladder; malformation; ectopic kidney